2007
DOI: 10.1111/j.1365-313x.2007.03397.x
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between JA, SA and ABA signalling during basal and induced resistance against Pseudomonas syringae and Alternaria brassicicola

Abstract: SummaryWe have examined the role of the callose synthase PMR4 in basal resistance and b-aminobutyric acid-induced resistance (BABA-IR) of Arabidopsis thaliana against the hemi-biotrophic pathogen Pseudomonas syringae and the necrotrophic pathogen Alternaria brassicicola. Compared to wild-type plants, the pmr4-1 mutant displayed enhanced basal resistance against P. syringae, which correlated with constitutive expression of the PR-1 gene. Treating the pmr4-1 mutant with BABA boosted the already elevated levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
232
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 275 publications
(250 citation statements)
references
References 43 publications
13
232
3
2
Order By: Relevance
“…The expected induction of the salicylic acid pathway in a compatible interaction and of the jasmonate pathway in an incompatible interaction (Zimmerli et al, 2004) was only confirmed for the wild-type plant. Deregulation of the jasmonate pathway in the pmr4 mutant was previously shown in the interaction with the necrotrophic pathogen A. brassicicola (Flors et al, 2008), which indicates that the callose synthase PMR4 might have not only an enzymatic function but also a regulatory role. Indeed, our data for the noncellulosic monocarbohydrate composition of the cell wall support the latter idea.…”
Section: Discussionmentioning
confidence: 99%
“…The expected induction of the salicylic acid pathway in a compatible interaction and of the jasmonate pathway in an incompatible interaction (Zimmerli et al, 2004) was only confirmed for the wild-type plant. Deregulation of the jasmonate pathway in the pmr4 mutant was previously shown in the interaction with the necrotrophic pathogen A. brassicicola (Flors et al, 2008), which indicates that the callose synthase PMR4 might have not only an enzymatic function but also a regulatory role. Indeed, our data for the noncellulosic monocarbohydrate composition of the cell wall support the latter idea.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier findings demonstrated that P. syringae-induced callose deposition is suppressed by ABA [14]. However, multiple studies from different groups have demonstrated that ABA exerts a positive influence on callose deposition after infection by fungi [23,28,49,50]. Moreover, it was recently demonstrated [50] that the fungal PAMP chitosan promotes ABA synthesis and that chitosan-induced callose is inhibited by pre-treatment with an ABA inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The spores were washed from the surface of the plate with inoculation medium (1 3 Gamborg B5 [Sigma], 10 mM Suc, 10 mM KH 2 PO 4 ; Flors et al, 2008), and fungal hyphae were removed from the suspension by filtering through four layers of cheesecloth. The concentration of spores was determined using a hemacytometer and adjusted to 1 3 10 5 spores mL 21 for A. brassicicola growth assays and 1 3 10 6 spores mL 21 for PME activity and qRT-PCR assays.…”
Section: Pathogen Strains Growth Conditions and Pathogen Growth Assaysmentioning
confidence: 99%
“…Prior to each experiment Alternaria brassicicola strain ATCC96836 was grown on a modified potato dextrose agar medium (Flors et al, 2008) for 10 d at room temperature. The spores were washed from the surface of the plate with inoculation medium (1 3 Gamborg B5 [Sigma], 10 mM Suc, 10 mM KH 2 PO 4 ; Flors et al, 2008), and fungal hyphae were removed from the suspension by filtering through four layers of cheesecloth.…”
Section: Pathogen Strains Growth Conditions and Pathogen Growth Assaysmentioning
confidence: 99%